2019
DOI: 10.1155/2019/9827403
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Mass Index and T-Scores of Bone Mineral Density in the Hip and Spine Regions among Older Adults with Diabetes: A Retrospective Review

Abstract: Diabetes mellitus (DM) cases are increasing worldwide, especially in Saudi Arabia. Previous studies suggested a positive relationship between body mass index (BMI) and bone mineral density (BMD) levels. Generally, patients with low BMI (<18.5 kg/m2) have reduced BMD levels and, thus, low T-scores; hence, they are categorized as osteopenic or osteoporotic. In this study, we aimed to determine whether a relationship between BMI and BMD T-scores in the hip and spine regions of patients with diabetes exists. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
3
16
0
1
Order By: Relevance
“…Another study also reported a similar finding 14 . The results were similar to other studies in the general population 37 - 41 . The mechanism of increased BMD in overweight or obese patients might be attributed to the increase in mechanical loading as well as elevated estrogen, leptin, and insulin, which induce osteogenesis and inhibit bone resorption 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Another study also reported a similar finding 14 . The results were similar to other studies in the general population 37 - 41 . The mechanism of increased BMD in overweight or obese patients might be attributed to the increase in mechanical loading as well as elevated estrogen, leptin, and insulin, which induce osteogenesis and inhibit bone resorption 42 .…”
Section: Discussionsupporting
confidence: 92%
“…Whereas T1DM is associated with modest reductions in bone mineral density (BMD) (Hip Z-scores of −0.37 ± 0.16) [19] and an increase in fracture risk [20], patients living with T2DM have higher BMD (Hip Z-scores of 0.27 ± 0.16 [19]) with an increased fracture risk [19,21,22]. This contradiction can be explained as follows.…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…As reported in many other studies, smaller body weight is associated with decreased bone size, which can increase the risk of fracture and osteoporosis. [26272829] In this study, the average body weight was smaller in patients with second fracture. In addition, the reason for the higher dementia rate in patients with second fracture may be that they have lower cognitive ability, gait, and sense of balance than those with primary fracture, resulting in a higher probability of falling and higher recurrence rate of fractures.…”
Section: Discussionmentioning
confidence: 55%